Overcoming indecision by changing the decision boundary - Malhotra, G; Leslie, D; Ludwig, C; Bogacz, R (American Psychological Association, 2017)
The dominant theoretical framework for decision-making asserts that people make decisions by integrating noisy evidence to a threshold. It has recently been shown that in many ecologically realistic situations, decreasing the decision boundary maximises the reward available from decisions. However, empirical support for decreasing boundaries in humans is scant. To investigate this problem, we used an ideal observer model to identify the conditions under which participants should change their decision boundaries with time in order to maximize reward rate. We conducted six expanded-judgement experiments that precisely matched the assumptions of this theoretical model. In this paradigm participants could sample noisy, binary evidence presented sequentially. Blocks of trials were fixed in duration and each trial was an independent reward opportunity. Participants therefore had to trade off speed (getting as many rewards as possible) against accuracy (sampling more evidence). Having access to the actual evidence samples experienced by participants enabled us to infer the slope of the decision boundary. We found that participants indeed modulated the slope of the decision boundary in the direction predicted by the ideal observer model, although we also observed systematic deviations from optimality. Participants employing sub-optimal boundaries do so in a robust manner, so that any error in their boundary setting is relatively inexpensive. The use of a normative model provides insight into what variable(s) human decision-makers are trying to optimise. Furthermore, this normative model allowed us to choose diagnostic experiments and in doing so we present clear evidence for time-varying boundaries